Education, race/ethnicity, and multimorbidity among adults aged 30-64 in the National Health Interview Survey - Vicki Johnson-Lawrence; Anna Zajacova; Rodlescia Sneed (Elsevier, 2017)
Background: Demographic risk factors for multimorbidity have been identified in numerous population-based studies of older adults; however, there is less data on younger populations, despite the fact that approximately 24% of US adults age 18+ have multimorbidity. Understanding multimorbidity earlier in the life course is critical because of the increased likelihood of long-term disability and loss of productivity associated with chronic disease progression. Objective: To examine the associations of education and race/ethnicity with mutimorbidity among adults aged 30-64 using cross-sectional data from the 2002-2014 National Health Interview Surveys. Design: Multimorbidity was defined as having at least 2 of 9 self-reported health conditions. Educational attainment was categorized as less than high school (HS), completed HS or some college, and bachelor's degree or higher. Logistic regression models of multimorbidity controlled for time since last doctor's visit, demographic and socioeconomic measures. Results: Compared to having a bachelor's degree or higher, completing less than HS (OR=1.58, 95% CI = 1.50-1.66) or HS/some college (OR=1.32, 95% CI = 1.27-1.37) were both associated with increased odds of multimorbidity net of all included covariates. Non-Hispanic Blacks had greater odds of multimorbidity (OR=1.07, 95% CI = 1.02-1.11) compared to Non-Hispanic Whites with comparable characteristics. Conclusions: Epidemiologic and demographic research on the burden of multimorbidity among non-elderly adults is limited, but warrants renewed attention given the potential for long-term loss of quality of life, productivity, and well-being for non-elderly adults. Reducing multimorbidity through health promotion efforts across the socioeconomic spectrum and earlier in the life course will be a requirement to age successfully and support overall well-being in the aging US population.